2012
DOI: 10.1039/c2an16126e
|View full text |Cite
|
Sign up to set email alerts
|

Probing gunshot residue, sweat and latent human fingerprints with capillary-scale ion chromatography and suppressed conductivity detection

Abstract: An investigation into capillary-scale ion chromatography with suppressed conductivity detection is presented for the identification of low molecular weight anions in samples of limited size. Both particle-packed and polymer monolith capillary ion exchange resins were compared with respect to their chromatographic efficiencies, operating back-pressures and thermal selectivities. Using a multistep hydroxide gradient, it was possible to separate a large selection of inorganic and organic anions in <23 mins using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…This correlates with our previous work using capillary IC, where this ion was similarly detected in sweat of smokers. However, no thiocyanate was detected in latent human fingerprints of these volunteers [32]. No quantifiable interference with any other GSRrelated ions was found in the sweat extracts studied here.…”
Section: Interferences In Alternative Matrices Relevant To Gsr Analysmentioning
confidence: 87%
See 1 more Smart Citation
“…This correlates with our previous work using capillary IC, where this ion was similarly detected in sweat of smokers. However, no thiocyanate was detected in latent human fingerprints of these volunteers [32]. No quantifiable interference with any other GSRrelated ions was found in the sweat extracts studied here.…”
Section: Interferences In Alternative Matrices Relevant To Gsr Analysmentioning
confidence: 87%
“…Quantitation of species deposited on the inner casing wall after discharge could act as a basis to study the degree of transfer to any external surface in future studies. In our previous study, it was found that the technique was successful in determining pg-fg levels of these species in deposited fingerprints on glass surfaces [32]. Depending on the level of use and area covered, these species on the hands are therefore likely to be present at much higher levels.…”
Section: Characterisation Of Gsr On Deposited On Ammunition Casingsmentioning
confidence: 97%
“…IEC exploits the diverse ion exchange affinities of different analytes toward a stationary phase for their separation . Similar to CE, IEC is utilized in a wide range of applications such as environmental analysis , bioanalysis , criminal investigations , and food analysis . Recently, there has been rapid progress in miniaturization of this technique, which resulted in modern instruments on the capillary‐scale (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…IEC exploits the diverse ion exchange affinities of different analytes toward a stationary phase for their separation [9]. Similar to CE, IEC is utilized in a wide range of applications such as environmental analysis [10,11], bioanalysis [12], criminal investigations [13,14], and food analysis [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been rapid progress in developing and miniaturization of this technique . This has resulted in commercially available capillary HPIC (cHPIC) instruments, which are able to detect analytes at trace levels …”
mentioning
confidence: 99%